MARKET ECONOMY MODEL OF UKRAINE EVOLUTIONIN MODERN CONDITIONS - KOVAL, Olexandr; MICHNO, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article describes concept of market economy model, process of a national market economy model formation and theoretical direction of this process. Market economy liberal model theoretical problems are highlighted, namely,  an uncertainty of market self-regulation and its theoretical underdevelopment. Social inequality is characterised as a sign of economy liberal model. Distribution of incomes both in the world and in Ukraine are analised.A market economy model evolution under influence of global historical events is highlighted. The libertarian model of the economy is presented, change in the economic model under the influence of the spread of Covid-19, the activation of certain actions of small and medium-sized businesses is characterised. Changes in the economic model under the influence of Russia's military invasion are identified, negative factors that had an impact are listed, and international aid for Ukraine's economy is described.Competition, as the central thesis of liberal economic policy, cannot fully fulfill tasks of economic system of society. Favorite variations of the "invisible hand of the market" of Adam Smith's time need revision. Therefore, it can be concluded that the liberal model of economy is characterised by social inequality, and its use can be revised in the direction of alternative, more optimal, models.
Keywords: market economy model; liberal market model; traditional market model; market self-regulation; libertarianism; social inequality; income distribution; digitalization